2019
DOI: 10.1080/21691401.2019.1649270
|View full text |Cite
|
Sign up to set email alerts
|

GPR39 agonist TC-G 1008 promotes osteoblast differentiation and mineralization in MC3T3-E1 cells

Abstract: Osteoporosis-related bone fracture and falls have a severe impact on patients' daily lives. Osteoblasts are bone-building cells that play a vital role in bone formation and remodeling. Imbalanced osteoblast differentiation could lead to osteoporosis. GPR39 is an orphan G protein-coupled receptor that mediates metabolic pathways. In this study, we show that GPR39 is expressed in MC3T3-E1 cells. Osteoblast differentiation culture media induces GPR39, suggesting that GPR39 is a differentiation-responsive factor. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…However, discussed results were inconsistent and contradictory, indicating that miR-21 may promote, as well as inhibit osteogenic differentiation, what can be correlated with diverse cellular plasticity of MSCs and their origin. To minimize this issue, we used the model of pre-osteoblast MC3T3 cell line that represents a stable and reproducible model for studies related with signaling pathways crucial for proliferation and differentiation of osteoblast [37][38][39][40][41]. Furthermore, under osteogenic conditions MC3T3 pre-osteoblasts synthesize and assemble collagenous extracellular matrix with organization and mineralization that resembles bone [37].…”
Section: Discussionmentioning
confidence: 99%
“…However, discussed results were inconsistent and contradictory, indicating that miR-21 may promote, as well as inhibit osteogenic differentiation, what can be correlated with diverse cellular plasticity of MSCs and their origin. To minimize this issue, we used the model of pre-osteoblast MC3T3 cell line that represents a stable and reproducible model for studies related with signaling pathways crucial for proliferation and differentiation of osteoblast [37][38][39][40][41]. Furthermore, under osteogenic conditions MC3T3 pre-osteoblasts synthesize and assemble collagenous extracellular matrix with organization and mineralization that resembles bone [37].…”
Section: Discussionmentioning
confidence: 99%
“…Along the cascade of AMPK activation, MF can influence its osteogenesis activity through Runx2 [37]. This will cause mature osteocyte formation and proper bone mineralization [38] Some studies prove these osteogenic effects. MF is shown to decrease bone turnover when compared with other anti-diabetic medications [48].…”
Section: Effect Of Metformin On Osteogenesis (Ampk-dependent Pathway)mentioning
confidence: 99%
“…AMPK induces these effects through the runt-related transcription factor Runx2 [37], which is vital for the maturation of chondrocyte and healthy skeletal formation [22]. Also, the inhibition of AMPK led to a decrease in the production of alkaline phosphatase, osteocalcin, and type-1 collagen, all of which are important for good quality bone formation [38]. It is also shown that AMPK inhibition would lead to decreased cellular activity of alkaline phosphatase and Runx2 [38].…”
Section: Ampk and Osteogenesismentioning
confidence: 99%
See 2 more Smart Citations